LEGAL PROTECTION FOR PATIENTS WHO EXPERIENCE LOSSES IN THE FIELD OF SERVICES MEDICAL DENTAL REVIEWED FROM THE LAW CIVIL - Irma Novianti; Dahlan; Tamaulina Br. Sembiring; Sumarno; Siti Nurhayati (PT. Radja Intercontinental Publishing, 2024)
Health services for patients by dentists are a right regulated by Law Number 36 of 2009 which has been changed to Law Number 17 of 2023 concerning Health. Patient rights are contained in Article 276 of Law Number 17 of 2023 concerning Health which aims to provide legal protection for patients, which is respected and implemented by health workers. This research aims to find out the regulations for dental health services in Indonesia, find out the legal relationship between dentists and patients in dental health services within the scope of civil law, and find out the legal protection for patients who experience losses in the dental field. services in civil law matters. The research method used in this research is normative juridical. The type of data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the research show that legal regulations regarding dental health services in Indonesia have been regulated in Law Number 36 of 2009 article 58 which has been changed to Law Number 17 of 2023 concerning Health article 193 which regulates dentist services for patients, Ministerial Regulations Republic of Indonesia Health Number 1419/MENKES/PER/X/2005 concerning the Implementation of services provided in Doctor and Dentist Practices. and Minister of Health Regulation No. 20 of 2016 shows the authority to provide dental and oral health services. The legal relationship between dentists and patients in dental health services within the scope of civil law begins with a vertical paternalistic relationship pattern. The relationship between a patient and a doctor is considered an agreement known as a therapeutic transaction in accordance with Law Number 17 of 2023 concerning Health. Legal protection for patients who experience losses in the field of dental health services in terms of civil law is regulated in articles 1320, 1338, 1365, 1366, and 1367. The Civil Code provides protection for consumers in the sense of patients with the aim of protecting the interests of patients.